Frontiers in Wastewater Treatment and Modelling FICWTM 2017 - Mannina, Giorgio (Lecture Notes in Civil Engineering,, 2017)
This book describes the latest research advances, innovations, and applications in the field of water management and environmental engineering as presented by leading researchers, engineers, life scientists and practitioners from around the world at the Frontiers International Conference on Wastewater Treatment (FICWTM), held in Palermo, Italy in May 2017. The topics covered are highly diverse and include the physical processes of mixing and dispersion, biological developments and mathematical modeling, such as computational fluid dynamics in wastewater, MBBR and hybrid systems, membrane bioreactors, anaerobic digestion, reduction of greenhouse gases from wastewater treatment plants, and energy optimization. The contributions amply demonstrate that the application of cost-effective technologies for waste treatment and control is urgently needed so as to implement appropriate regulatory measures that ensure pollution prevention and remediation, safeguard public health, and preserve the environment. The contributions were selected by means of a rigorous peer-review process and highlight many exciting ideas that will spur novel research directions and foster multidisciplinary collaboration among different water specialists. .